Reclaiming Identity: Vernacular Feminism in Gita Hariharan’s The Thousand Faces of Night - Yogini B. Kelaiya; Dr. Iros Vaja (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2023)
Gita Hariharan's novel, The Thousand Faces of Night, has significant importance within the Indian literature as it extensively explores the intricate nature of identity and the multifarious challenges faced by women in a patriarchal Indian social structure. This study examines the intricate depiction of vernacular feminism in the novel, elucidating the many methods through which female characters defy conventional gender roles and standards. The novel's plot takes place within the vibrant metropolitan setting of post-independence India, effectively depicting the fundamental aspects of cultural variety and the conflict between traditional values and contemporary ideals. Hariharan provides insight into the subtle but impactful forms of resistance that take place inside household environments, as shown via the experiences of the female characters. These women, hailing from diverse socio-cultural origins, adeptly negotiate the intricacies of their life while claiming their agency and distinctiveness. This study investigates the use of vernacular feminism by Gita Hariharan as a narrative device to portray female characters that actively oppose subjugation, challenge societal inequities, and reinvent their sense of self in the midst of challenging circumstances. This study examines the narratives of the characters in the book, with a focus on their processes of self-exploration and attainment of agency. The analysis also takes into account the influence of the vernacular feminism shown in the novel on the wider conversation around feminism in India, as well as its consequences for the overarching endeavor to achieve gender equality.